KOMPETENSI KOMUNIKASI KEMITRAAN BIDAN DESA DAN DUKUN BAYI DALAM MENDUKUNG PENURUNAN ANGKA KEMATIAN IBU DAN BAYI - Ernawati Koto (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2020)
The purpose of this study is to analyze the communication competence of village midwives and TBAs in supporting the decrease of maternal and infant mortality rate and to analyze the efforts of village midwives and TBAs in maintaining partnership in Singkohor sub-district of Aceh Singkil district. The method used is qualitative method with constructivist paradigm. Data were collected based on in-depth interviews on 6 informants consisting of 3 village midwives and 3 dukun bayi. The results showed that the midwives 'midwives' partnership and midwife communications process worked well. The communication competence of village midwives and midwives is seen from the motivation, knowledge and skills indicate that the motivation of the village midwife to partner with the dukun baby is due to the belief and closeness of the community to the midwife whose knowledge is gained from the experience passed down from generation to generation while the shaman has motivation partnering with the village midwife because the TBA believes in the credibility of midwives in handling childbirth where knowledge is gained from the learning process.